Геоинформационная оценка деградации степных и полупустынных ландшафтов юга европейской части России - Калинчук, И.В.; Мирошниченко, И.А.; Михайлов, В.А.; Позаченюк, Е.А.; Рулёв, А.С.; Юферев, В.Г. (Культура народов Причерноморья, 2014)
Деградированные земли являются экологически опасными природными объектами, так как,
переставая выполнять свои природно-хозяйственные функции, могут провоцировать процессы
опустынивания. Современным методом, позволяющим установить деградацию пастбищных ландшафтов,
является картографо-аэрокосмический на основе ландшафтной ГИС. Геоинформационная оценка
проективного травянистого покрытия по космоснимкам базируется на определении фототона
изображения и параметров распределения пикселей, что позволяет определить урожайность травостоя и
уровень деградации пастбищ. Деградовані землі є екологічно небезпечними природними об'єктами, тому що, перестаючи
виконувати свої природно-господарські функції, можуть провокувати процеси спустелювання. Сучасним
методом, що дозволяє установити деградацію пасовищних ландшафтів, є картографо-аерокосмічний на
основі ландшафтної ГИС. Геоінформаційна оцінка проективного трав'янистого покриття по космознімках
базується на визначенні фототону зображення й параметрів розподілу пікселів, що дозволяє визначити
врожайність травостою й рівень деградації пасовищ. Degraded lands are environmentally hazardous natural objects, because they fail to fulfill their natural
and economic functions and can initiate processes of desertification. This poses an essential danger to other
components of ecological systems and the environment as a whole, including the conditions of human life support.
Desertification processes cover large areas of the south of European Russia, especially in the Astrakhan region.
Further land using in these areas is impossible without a comprehensive assessment of the level of degradation,
mapping and monitoring. Modern method to detect degradation of pasture landscapes, is the method of cartographic
and aerospace researches based on landscape geoinformation system. Geoinformation assessment of projective
herbaceous cover by the satellite images makes possible the determination both the level of image's phototone and
parameters of pixels spreading and at the same time it is the complex indicator, which allows to determine the
productivity and projective cover of grass canopy, and the level of pasture areas degradation in general.
Degradation assessment arises from photo-verification key areas with the definition of the average value of the
phototone range for each type of soil on four levels: «disaster», «risk», «crisis», «norm».